The Impact of Marketing Mix on Patient Loyalty and Satisfaction in Inpatient Services - Indah Sri Astuti; Burhannudin Ichsan; Muzakar Isa (Universitas KH. Abdul Chalim Mojokerto, 2025)
The impact of the marketing mix appeared to be one of the most important elements in influencing patient loyalty and satisfaction. The marketing mix consists of many variables, namely product, price, place, promotion, physical evidence, and process. Building on well-known frameworks such as the SERVQUAL model and the Theory of Planned Behaviour, this study suggests a mediating role of patient satisfaction between specific marketing mix elements and loyalty. A quantitative technique was used and data was collected from inpatients using structured questionnaires. The results show that physical evidence and process have a positive and significant effect on satisfaction and loyalty; however, the effect of product, price, place, and promotion on loyalty is direct and not mediated by satisfaction. These findings are consistent with previous literature emphasizing the role of service quality and customer experience in the healthcare setting. However, the study does not focus on any other specific methodology to identify other factors that can predict a patient's satisfaction in a hospital environment. It provides a theoretical and practical basis for future health service marketing movements.